A comparative study of the quality differences and seasonal dynamics of flavonoids between the aerial parts and roots of Scutellaria barbata - Cheng, Yijie; Cao, Wenxin; Guo, Ru; Chen, Ruihuan; Li, Xiaofan; Qian, Da; Xu, Jingyuan (Frontiers in Plant Science, 2024)
Scutellaria barbata D. Don (S. barbata) is a widely cultivated Chinese herbal medicine known for its medicinal properties. However, differences in the spatial distribution of metabolites, accumulation patterns of flavonoids, and pharmacological activities between the aerial parts and root of S. barbata still remain unclear, posing challenges for its standardized cultivation and quality control. This study aimed to elucidate the quality differences between these plant parts and clarify their seasonal variations. In this research, there were 46 compounds identified in S. barbata that included 44 flavonoids. Although S. barbata is rich in flavonoids, the distribution of flavonoids between the aerial parts and root was significant differences. The aerial parts primarily accumulate flavonoids with 4' hydroxyl groups, while the underground parts mainly accumulate flavonoids lacking these groups. Additionally, the accumulation and variation of flavonoid components were seasonally dependent, with the aerial parts reaching peak content in spring during vigorous vegetative growth, and the roots accumulating most flavonoids in autumn. The extracts from both parts exhibited antioxidant activity and inhibitory effects on cancer cell proliferation, with notable differences between them. This study provides valuable insights into the quality differences and seasonal dynamics of the different parts of S. barbata, offering a reference for standardized harvesting and quality control.